Persepsi Mahasiswa Terhadap Konten Kesehatan Mental Tiktok Pada Pembentukan Karakter Positif Di Universitas Palangka Raya - Andika Dimas Yogatirta; Ade Adharianto; Bhayu Rhama; Fitriana Selvia (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of students' perceptions of mental health content on TikTok on the formation of positive character at the University of Palangka Raya. The research question asked is how significant are students' perceptions of mental health content on TikTok in influencing the formation of positive character? The study uses a quantitative descriptive approach with correlational techniques. A sample of 122 students from 8 faculties at Palangka Raya University was determined through proportional random sampling. Data were collected using a structured questionnaire and analyzed with SPSS version 27 through validity, reliability, simple linear regression, t-test, and coefficient of determination (R²) tests. The research hypothesis states that there is a significant effect of students' perceptions of mental health content on TikTok on positive character formation. The results show that students' perceptions have a significant effect on positive character formation with a t-value of 10.251 > t-table 1.98 and significance 0.000 < 0.05. The coefficient of determination (R²) of 0.467 indicates that 46.7% of the variation in positive character formation can be explained by student perceptions. These findings confirm that mental health content on TikTok can be an effective educational tool for developing empathy, self-awareness, and emotional control among Generation Z, although excessive use remains mental health risk.